Patient-Reported Roles in Decision-Making Among Asian Patients With Advanced Cancer: A Multicountry Study - Semra Ozdemir (SAGE Publishing, 2021)
Purpose. We investigated 1) perceived roles in decision-making among advanced cancer patients in 5 Asian countries 2) associations of patient characteristics with these roles, and 3) the association of perceived roles with quality of life and perceived quality of care. Methods. We surveyed 1585 patients with stage IV solid cancer. Multinomial logistic regressions were used to analyze associations of patient characteristics with decision-making roles. Multivariate regressions were used to analyze associations of decision-making roles with quality of life and care. Results. The most common perceived-role was no patient involvement. Most patients (73%) reported roles consistent with their preferences. Being male, nonminority, higher educated, aware of advanced cancer diagnosis, and knowledge of cancer diagnosis for ≥1 year were associated with higher levels of patient involvement in decision-making. Compared to no patient involvement, joint decision-making (together with physicians/family) was associated with higher social (β = 2.49, P < 0.01) and spiritual (β = 2.64, P < 0.01) well-being, and better quality of physician communication (β = 9.73, P < 0.01) and care coordination (β = 13.96, P < 0.01) while making decisions alone was associated with lower emotional (β = −1.43, P < 0.01), social (β = −2.39, P < 0.01), and spiritual (β = −2.98, P < 0.01) well-being. Conclusions. Findings suggest that a substantial number of advanced cancer patients were not (and preferred not to be) involved in decision-making. Despite this finding, joint decision-making together with physicians/family was associated with better quality of life and care. Implications. Physicians should explain the benefits of shared decision making to patients and encourage participation in decision-making, while ensuring that patients feel supported and do not find decision-making overwhelming.